Life Threat and Sleep Disturbances in Adolescents: A Two‐Year Follow‐Up of Survivors From the 2011 Utøya, Norway, Terror Attack. Issue 3 (6th June 2017) - Grønli, Janne; Melinder, Annika; Ousdal, Olga Therese; Pallesen, Ståle; Endestad, Tor; Milde, Anne Marita
Abstract : A significant number of adolescents have been exposed to traumatic life events. However, knowledge about the specific sleep disturbance that occurs in individuals after trauma exposure is predominantly based on studies of adults. This study reports specific sleep disturbance in 42 survivors of the 2011 mass shooting at a youth summer camp on the Norwegian island Utøya, mean age = 20.91 years, SD = 2.32, 62.5% females. When compared with matched controls, significantly more survivors reported having sleep disturbances, 52.4% versus 13.6%, d = 0.93, of which onset began at the time of the shooting, χ 2 = 14.9, p < .001. The prevalence of insomnia, 56.3% versus 11.0%, d = 0.73; excessive daytime sleepiness, 34.4% versus 13.6%, d = 0.61; symptoms of obstructive sleep apnea, 18.8% versus 0%, d = 0.70; and frequent nightmares, 37.5% versus 2.3%, d = 0.90, were all higher in the survivors than in the controls. In a subgroup of survivors (n = 20) with psychiatric diagnoses, sleep disturbances were more prevalent than in survivors without psychiatric diagnosis. Actigraphy data revealed delayed bedtime, sleep onset, and rise time in survivors compared with controls, t s > 1.7, p s = .044 to .028. These results corroborate the effects of a life threat on the range and extent of sleep disturbances, and emphasize the need to better assess and treat sleep disorders in adolescents exposed to trauma.